Innovative Training Strategies for Public Response to Out-of-Hospital Cardiac Arrest: A Scoping Review - Dalle H; Trisyani Y; Nur'aeni A (Risk Management and Healthcare Policy, 2025)
Heriyansyah Dalle,1 Yanny Trisyani,2 Aan Nur’aeni2 1Postgraduate Program of Nursing, Faculty of Nursing, Universitas Padjadjaran, Sumedang, West Java, Indonesia; 2Department of Emergency and Critical Care Nursing, Faculty of Nursing, Universitas Padjadjaran, Sumedang, West Java, IndonesiaCorrespondence: Aan Nur’aeni, Faculty of Nursing, Universitas Padjadjaran, Jl. Raya Ir. Soekarno KM. 21, Hegarmanah, Jatinangor, Sumedang, West Java, 45363, Indonesia, Tel +6285624217006, Email aan.nuraeni@unpad.ac.idIntroduction: Out-of-hospital cardiac arrest (OHCA) is a critical medical emergency requiring immediate intervention to improve patient outcomes. Training the lay public in emergency intervention techniques has significantly enhanced survival rates. Easily accessible training programs are essential for equipping individuals with the necessary knowledge and skills. However, challenges such as standardized guidelines and cost-effective program delivery must be addressed. This study aimed to explore innovative practices in training and provide recommendations for enhancing emergency response capabilities in OHCA.Methods: The PRISMA Extension for Scoping Reviews (PRISMA-ScR) framework guided a comprehensive scoping review to identify relevant literature from PubMed, ScienceDirect, Scopus, EBSCOhost, and one search engine, Google Scholar. JBI tools were utilized to select high-quality articles, and thematic analysis was conducted to identify relevant innovations in OHCA training.Results: This review analyzed 13 articles discussing various methods of CPR training for the general public, considering cost, ease of use, and effectiveness. The findings highlight innovative approaches to improving the public’s emergency response to OHCA. Smartphone apps significantly increase the likelihood of CPR and defibrillator use by laypersons. Low-cost DIY manikins are a viable alternative when resources are limited. Short CPR training videos and hands-only CPR training proved effective in training lay responders, while feedback devices and XR and VR-based training increased participants’ confidence in CPR. Policy-based approaches, such as mandated CPR training, can broadly increase training coverage. Although advanced technologies offer high effectiveness, the cost and complexity of implementation remain significant challenges.Conclusion: The study provides valuable insights for developing innovative and effective training strategies to improve community emergency response to OHCA. However, further research should focus on long-term evaluation and integrating innovative technologies with low-cost training methods to develop more standardized and contextually appropriate training guidelines.Keywords: emergency response, out of hospital cardiac arrest, public training